2017
DOI: 10.1089/met.2016.0104
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofMYD88in Adipose Tissue of Obese People: Is There Some Role in the Development of Metabolic Syndrome?

Abstract: Background: The mechanism leading to the development of metabolic complications in obese individuals is not fully understood. Thus, the objective of this study was to examine differences in insulin resistance, inflammation, cytokine and adipokine levels, and expression of selected genes across obese individuals with different number of metabolic syndrome (MetS) components. Methods: Forty obese individuals who underwent bariatric surgery, divided in three groups based on the number of components of MetS, in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…While dectin-1 knockout in the bone marrow of LDLR −/− mice did not alter the progression of atherosclerosis ( 68 ), a recent study found that dectin-1 signaling enhanced obesity and insulin resistance in mice with in MyD88 knockout mice fed a high fat diet ( 69 ). In humans, expression of MyD88 has been associated with obesity and metabolic syndrome ( 70 ). Dietary supplementation with laminarin-reduced hepatotoxicity in rats treated with lipopolysaccharide (LPS), suggesting an anti-inflammatory effect for some formulations of laminarin ( 71 ).…”
Section: Laminarin Sulfatementioning
confidence: 99%
“…While dectin-1 knockout in the bone marrow of LDLR −/− mice did not alter the progression of atherosclerosis ( 68 ), a recent study found that dectin-1 signaling enhanced obesity and insulin resistance in mice with in MyD88 knockout mice fed a high fat diet ( 69 ). In humans, expression of MyD88 has been associated with obesity and metabolic syndrome ( 70 ). Dietary supplementation with laminarin-reduced hepatotoxicity in rats treated with lipopolysaccharide (LPS), suggesting an anti-inflammatory effect for some formulations of laminarin ( 71 ).…”
Section: Laminarin Sulfatementioning
confidence: 99%
“…This interaction activates a family of kinases which in turn activate different molecules including NFκB, a primary transcription factor. The translocation of NFκB to the nucleus upregulates the production of INF and inflammatory cytokines, which is an evidence that these receptors play a role in the immune system [53,54].…”
Section: Inflammationmentioning
confidence: 97%
“…ese methods have different effects on different age groups of obese people, and the effect of teenagers is better than that of teenagers and middle-aged people. VLCDs at 3-4 months can reduce body weight by 15%-25%, but the long-term effect is still controversial [10].…”
Section: Effect Of Medicinal Plant Intervention On Physical Fitnessmentioning
confidence: 99%